An Effective Combination for Holistic Health: Omega-3 Fatty Acid and Ayurvedic Herbs - Dr. Navneet (Revista Electronica de Veterinaria, 2023)
Essential nutrients, omega-3 fatty acids are well-known for their many health advantages, which include heart health, cognitive function, and anti-inflammatory qualities.  Omega-3 fatty acids are polyunsaturated fats that are vital to human health and have been extensively researched for their possible advantages in neuroprotection, inflammation reduction, cardiovascular health, and general physiological well-being.  Although fish oil has historically been the source, flaxseeds, chia seeds, and walnuts are all common plant-based omega-3 sources.  Because of their anti-inflammatory, cardiovascular, and cognitive health advantages, omega-3 fatty acids are essential nutrients. Herbs and plant-based diets are natural sources of omega-3 according to Ayurveda, the traditional Indian medical system.  This study examines the synergistic benefits of omega-3-rich Ayurvedic herbs and how they can improve general health.  Additionally, based on current scientific research, this study examines the physiological roles, dietary sources, biochemical makeup, and therapeutic importance of omega-3 fatty acids.